2022
DOI: 10.3390/nu14193967
|View full text |Cite
|
Sign up to set email alerts
|

Does the Gut Microbial Metabolome Really Matter? The Connection between GUT Metabolome and Neurological Disorders

Abstract: Herein we gathered updated knowledge regarding the alterations of gut microbiota (dysbiosis) and its correlation with human neurodegenerative and brain-related diseases, e.g., Alzheimer’s and Parkinson’s. This review underlines the importance of gut-derived metabolites and gut metabolic status as the main players in gut-brain crosstalk and their implications on the severity of neural conditions. Scientific evidence indicates that the administration of probiotic bacteria exerts beneficial and protective effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 258 publications
0
13
0
Order By: Relevance
“…The age-related microbial imbalance of the gut microbiome contributes to the development of oxidative stress and inflammation that underlie arterial dysfunction. Such findings, therefore, support that good gut microbiota helps prevent cardiovascular disease [ 2 ].…”
Section: Introductionmentioning
confidence: 65%
“…The age-related microbial imbalance of the gut microbiome contributes to the development of oxidative stress and inflammation that underlie arterial dysfunction. Such findings, therefore, support that good gut microbiota helps prevent cardiovascular disease [ 2 ].…”
Section: Introductionmentioning
confidence: 65%
“…One of the consequential effects of gut dysbiosis is its wide-ranging effects on gut-derived metabolites. These metabolites often play a significant role in modulating inflammatory responses and the chronicity of symptoms [ 27 ]. In order to focus on a gut microbiome-directed approach in identifying modulators of inflammation and potential therapeutic targets [ 28 ], we performed a global metabolomics analysis using the fecal samples of the same groups, namely, Chow, Chow + GWI, WD, and WD + GWI.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic agents augment an improvement of depression symptoms and stress-related diseases modulated by stress hormones and cytokines release [ 49 ] in conjunction with microbiota influencing the ability of neurons, brain tissue and immune cells to regulate inflammation [ 50 ]. Clinical and experimental data have indicated that the probiotics induce positive impacts upon the central nervous system [ 51 , 52 ]. Probiotics were shown to reduce CNS inflammatory processes and activation of microglia, decreasing neuroinflammation, probably through the production of the brain-derived neurotrophic factor (BDNF) and the improved synaptic plasticity, related to an increased concentration of postsynaptic density protein 95 (PsD95) [ 53 ] A randomized, double-blind, and controlled clinical trial on AD patients showed that a 12-week probiotic treatment induced a significant improvement in the MMSE score and a significant decrease in plasma malondialdehyde in the probiotic-treated group [ 54 ].…”
Section: Discussionmentioning
confidence: 99%